On President Rodrigo Duterte's "War on Drugs" its impact on the diplomatic regime in the Asia-Pacific region - Lopega, Diosdado B. (2019)
This study looks into the "War on Drugs" of the Duterte administration. As can be gathered from the Philippine National Police (PNP) Command Memorandum Circular (CMC) No. 16-2016, the drug problem continues to breed social ills in the country. Also, the Department of the interior and Local Government (DILG) Memorandum Circukar 2017-112 seeks to heighten the level of awareness on corruption, illegal drugs, criminality the violent extremism and other threats to peace and security. With these official pronouncements, the government is apparently convinced that the drug problem must be curbed. When Duterte was sworn in as the 16th president of the Philippines on June 30, 2016, he immediately unleashed his "War on Drugs". This war has been followed by killings of people who were suspected of being drug users, drug pushers and drug dealers.